SELF-LIBERATION IN JODI PICOULT’S MY SISTER’S KEEPER - Rosa Maria Simamora; Yolanda Silaban (Muse: Jurnal of Art, 2023)
The research is self-liberation in Jodi Picoult’s My Sister’s Keeper. The novel represents people especially teenagers who want to liberate themselves from parents’ power, unfair treatment, fear and feeling guilty, to get medial emancipation and through sisterhood. This is a library research and applies mimetic theory proposed by Abrams saying that literature is an imitation of the real world. Liberation from parents' power is represented by Anna when she liberates herself by suing her mother because of making her as a donor to save her sister. Liberation from parents’ unfair treatment is represented by Anna and Jesse. Anna feels that she is treated unfairly by her mother because her mother has born Anna just for Kate needs a donor, and Jesse feels that he is treated unfairly because he does not get his parents’ attention. Liberation from fear and feeling guilty is represented by Sara and Campbell. Sara who is initially afraid of losing her daughter, Kate, is finally able to accept the reality and also feels guilty when Anna died because she had made Anna as a donor for Kate. Campbell liberates himself from his fear and over-thinking, he realizes that he has been wrong for hiding his epilepsy from the people around him, especially Julia. Liberation to get medical emancipation is represented by Anna and Kate. Anna wants to liberate herself to get medical emancipation so she can survive without having to donate anything to Kate. Kate wants to liberate herself to get her medical emancipation through Anna to refuse any kind of medical treatments because of giving up living. Liberation through sisterhood is represented by Anna who liberates herself because her sister, Kate forbids her to donate her kidney so Kate can go peacefully and Anna can live a normal life without having to worry about Kate anymore. In conclusion, the author, Jodi Picoult in her novel My Sister’s Keeper vividly portrays the condition of people who have right to possess their bodies even though they have to take legal action to sue families to get mutual understanding and advantages.